AN ANALYSIS OF MORAL VALUE IN SHORT STORY “THE LAST LEAF” BY O HENRY - Syahada Nurul Ummah; Eripuddin; Pipit Rahayu (English Study Program University of Pasir Pengaraian, 2020)
This research discussed about the moral values as found out in the last leaf short story. Moral values were found out by using sociological theory. This research used method descriptive qualitative. This instrument used was the short story of The Last Leaf. The researcher also used other information about moral values. Researchers also use the theory of moral values in orderto better know what moral values are contained in the short story of The Last Leaf. Based on the sociological approach, there are three perspectives: functional perspective, symbol perspective, conflict perspective. After analyzing the researcher found some moral values, namely Tolerance, Fairness, Belief, Kind-hearted, honesty, and responsibility.